Detection of Antimicrobial Compounds Isolated from Several Tropical Lentinus by Bioautographic Method - LISDAR I. SUDIRMAN (HAYATI Journal of Biosciences, 2005)
The antimicrobial compounds extracted either from culture filtrates or mycelia of several tropical Lentinus species could be detected their existences and locations by bioautographic method. For this purpose, the crude extracts were deposited as spots on silica gel plates and developed in a n-butanol-acetic acid-water mixture (3:1:1). The dry silica gel plates were then seeded with Bacillus subtilis and incubated at 35 oC for one night. On these plates, the extracts were separated into several bioautographic spots or growth inhibition zones. In parallel, the spots were detected by viewing with chemical revelations or under ultraviolet radiations at 254 nm or 366 nm. On silica gel thin-layer chromatograms, the crude extracts of Lentinus were separated into several bioautographic spots; for the filtrate extracts of L. squarrosulus 55A into three spots (Rfs 0.75, 0.50, 0.17), the mycelial extracts of L. sajor-caju LSC8 into two spots (Rfs 0.77, 0.54), the mycelial extract of L. torulosus LU3 into two spots (Rfs 0.77, 0.48), the filtrate extracts of L. cladopus LC6 into one spot (Rf 0.76) but the mycelial extracts of this mushroom separated into two spots (Rfs 0.79, 0.54), the filtrate and mycelial extracts of L. cladopus LC4 into three spots respectively (Rfs 0.75, 0.61, 0.45 for the filtrate extract and Rfs 0.83, 0.73, 0.60 for mycelial extract). By this method, the active compounds were detected directly and it is a usual method for further work on the purification of the target compounds.